Hélio Oiticica, Propositor de Práticas: Teoria Crítica sobre o Parangolé, Nova Objetividade e Tropicália (Palíndromo, 2013)
The present work aims to understand the theories that guided the production of the artist Hélio Oiticica. According to the texts that were written between 1959 to 1969, Oiticica was one of the few artists who theorized, conceptualized, art itself. The artist's idea was to secure key questions in the field of art. The more writing, more potencializava his theory that will accompany each work and invention. From this study, theoretical points raised were the work of Helio Oiticica, noting the theoretical potential that was created to design what was a work of art. Parangolé, Nova Objetividade and Tropicalia texts were used to extract the concepts filóficos adopted by the artist. Since the text is taken from Anne Cauquelin possible theories used by Hélio. Are analyzes of the speech of an artist with the orientation of critical theory.
Keywords: Critical theory; Helio Oiticica; parangolé; nova objetividade; tropicália; practices